Chemical insights into the synthetic chemistry of five-membered saturated heterocycles—a transition metal–catalyzed approach - Sunbal,; Alamzeb, Muhammad; Omer, Muhammad; Abid, Obaid-Ur-Rahman; Ullah, Mohib; Sohail, Muhammad; Ullah, Ihsan (Frontiers in Chemistry, 2023)
Drug designing and delivery is primarily based on hunt for new potent drug candidates and novelty in synthetic techniques. Recently, saturated heterocycles have gained enormous attention in medicinal chemistry as evident from the medicinal drugs listed in the FDA Orange Book. Therefore, the demand for novel saturated heterocyclic syntheses has increased tremendously. Transition metal catalyzed reactions has remained the prime priority in heterocyclic syntheses for last three decades. TM catalysis has nowadays been well adorned by combining it with other techniques like bio and / or enzyme catalyzed reactions or organocatalysis or using two different metal metals in a single catalysis. This review highlights the recent developments of transition metal catalyzed synthesis of five-membered saturated heterocycles.